Analisis Strategi Pengembangan Fasilitas Di Pelabuhan Perikanan Kluwut, Kabupaten Brebes - Aulia M. Hasanah; Noor Zuhry; Beni S. Nugroho (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2026)
The Kluwut Fisheries Port facilities in Brebes Regency are an important element in supporting capture fisheries activities, but their availability and condition are not yet fully optimal. This study aims to analyze the existing condition of the facility and formulate a development strategy. The method used is descriptive with a quantitative and qualitative approach through primary and secondary data collection. Primary data was obtained through observation, interviews, and documentation of 30 respondents, while secondary data came from related agencies. The analysis was conducted using a Likert scale, pair comparison against regulatory standards, and SWOT analysis. The research results show an increase in fisheries production, production value, and the number of vessels during the 2023–2025 period, reflecting the growth of fisheries activities. The condition of port facilities is generally in the fair to good category, with relatively adequate functional and supporting facilities. However, several main facilities are still not optimal, such as the Fish Auction Place (TPI) and sanitation facilities, and the level of facility availability does not meet the standards of Minister of Maritime Affairs and Fisheries Regulation No. 8 of 2012. The SWOT analysis places the port in quadrant I (Strength–Opportunity), which indicates that internal strengths can be leveraged to capture external opportunities. The development strategy is focused on optimizing institutional support, improving service quality, reactivating TPI, and developing facilities in a gradual and sustainable manner to improve port operational performance and effectiveness.